The self-efficacy of education students in understanding materials and mathematical problem-solving - Baiduri, Baiduri; Usmiyatun, Usmiyatun (International Journal of Evaluation and Research in Education (IJERE), 2025)
The present study investigates the self-efficacy (SE) of education students concerning their understanding of educational materials and mathematical problem-solving skills. SE, a crucial motivational construct, plays a vital role in academic achievement and cognitive development. The research employed a quantitative approach, utilizing a structured questionnaire to collect data from 155 mathematics education students and 67 biology education students. The questionnaire using a Likert-type scale comprised two main sections: one assessing SE beliefs related to understanding educational materials and the other focusing on SE beliefs associated with mathematical problem-solving. The data analysis was performed using descriptive and inferential statistical methods, including correlation analysis and independent t-tests by JASP 0.16.3.0. The findings provide valuable insights into the SE of education students in the context of different disciplines. The study reveals the overall SE levels of mathematics and biology education students in understanding educational materials and mathematical problem-solving are moderate level. There is no significant relationship between the SE of mathematics and biology education students in understanding materials and mathematical problem-solving. However, there are significant differences in SE for both understanding materials and mathematical problem-solving between the two groups. The implications of these findings for instructional practices are discussed.